Congruity and Incongruity between Pratham Patala Gata Timir and Myopia - Lakra, Medha (International Journal of Pharmaceutical & Biological Archive, 2022)
Eye diseases are much more important than any other physical disability, because once the vision is lost then that person is disabled for doing all regular activities; day and night are same for the person. Timir is a disease, which starts with simple visual disturbances (Avyakta Darshana) but if unattended, it may lead to ends in profound loss of vision. According to site of lesion, Acharya Sushruta has explained 76 Netravyadhi among them vision-related disorders are studied under broad heading of “Drishtigata roga.” The pathogenesis of Timir has been described in terms of involvement of successive Patalas (Layers). Blurring of vision is the only clinical features found in Pratham Patala (first layer) and it is also cardinal sign of myopia in Modern science. Uncorrected refractive errors are the one of the most important causes of vision impairment and the leading cause of blindness in the developing countries. Although there is availability of advanced technological aids such as spectacles, contact lenses and lasik surgeries but limitations are there due to certain adverse effects, cost effectiveness etc. Hence, Ayurvedic science can be explored to find a better alternative to manage this condition. In Ayurveda, there are number of preventive and curative modalities explained to treat Timir in the form of Pathykaraahar-vihar, Rasayana Yoga, Chakshushya drugs, Netra karma, Kriyakalpa, Panchkarma, etc.